Quantum sensor using guided matter waves in optical fibers - Xin, Mingjie (2019)
Coherent interaction between matter waves and light is the core of quantum sciences and technologies. In the optical domain, coherent manipulation of quantum states of atoms using light has been employed in applications such as precision metrology, quantum simulation, quantum computing, etc. Miniaturizing technologies of atom-light-based quantum systems for practical applications has been a longstanding goal since their development. However, the diffraction nature of light has limited the scalability of the quantum systems. Highly sensitive light-pulse atom interferometers in free space are tens of centimeters in size and, therefore, they are hardly being used in micro-scale systems for wide applications. In this work, we optically trap cold 85Rb atoms inside a hollow-core photonic crystal fiber and use the optical waveguide mode inside the micro-scale structure to manipulate atoms as beamsplitter and mirror pulses to form an inertia-sensitive atom interferometer which can be used to measure the gravitational acceleration g. Further, the atom interferometer is not limited by the diffraction nature of the light. Coherent interaction between a waveguide mode and a quantum system, could lead to constructing mobile and miniature quantum hybrid platforms for precision measurement and quantum sensing. This work is related to and can be applied to a wide range of disciplines, including photonics, fundamental physics, and quantum sensor technology. Moreover, the dephasing mechanism of quantum superposition states of the atoms and the transportation of quantum superposition inside the fiber are studied. We demonstrate coherent guiding of ground-state superpositions of 85Rb atoms over a centimeter range and over hundreds of milliseconds inside a hollow-core fibre. The transportation distance is limited by the inhomogeneity of ambient magnetic field in our apparatus and not by the fiber structure. Our experiment establishes an important step towards a versatile platform that can bring long-lived quantum spin coherence outside the traditional bulky apparatus and over variable distances. This can lead to applications in quantum information networks and matter wave circuit for quantum sensing.